Medidas de biosseguridade e controle da laringotraqueíte aviária nas granjas do município de Guatapará, estado de São Paulo - Farra, Maria Carolina Teixeira Dal [UNESP] (2014)
This present work has not only evaluated the implementation of biosecurity measures on poultry farms in response to the sanitary educational work program, conducted in Mombuca Colonial Nucleus, in the city of Guatapará, state of São Paulo/Brazil, by the Agriculture Defense Coordinating Council (ADCC) of the Secretariat of Agriculture, but also established relationship with obtained laboratory results. In order to achieve that, an epidemiological inquiry was conducted in December of 2010, in which 19 poultry farmers were interviewed with the purpose of obtaining information of epidemiological interest. In addition, 30 tracheal swabs were taken from all the properties at 3 different times: in December of 2010, before the start of the vaccination with attenuated vaccine, in November of 2011, and in March of 2013, after the start of the vaccination; thereafter, they were sent to the Biological Institute of Descalvado, where were subjected to the laboratory test Polymerase Chain Reaction (PCR) in order to detect the presence of the infectious laryngotracheitis virus (ILT). The chosen sanitary education model was the dialogical approach through orientation and clarification on doubts in the properties. The diagnosis of implanted biosecurity measures was conducted through the ‘checklist’, applied by the ADCC representatives on poultry farms of Mombuca Colonial Nucleus, in May of 2010. In July of 2010, two months after the initial evaluation, the properties were controlled with the purpose of verifying the maintenance of previous implemented measures. The second revaluation with the checklist application on poultry farms was conducted after two years of the initial evaluation, in May of 2012. The actions of the sanitary education strongly influenced the implementation of the biosecurity measures. Associations between adoption of biosecurity measures and report of respiratory disease by ...